(untitled) (Current Problems in Rail Vehicles, 2025)
The article deals with the phenomenon of torsion oscillations in a fully-suspended drive of a locomotive. Specifically, it focuses on excited resonance states of a membrane coupling and a pinion and on their sensitivity on torsion stiffnesses of adjacent torsion springs. The source of excitation of this resonance oscillations are harmonic components of the electromagnetic torque of a traction asynchronous motor. Subsequent research, presented in this article, is further oriented on investigation of elimination possibilities of the resonance states via retuning of torsion stiffnesses of specific torsion springs. These represents a rotor shaft and a membrane coupling in the real fully-suspended drive.